2008
DOI: 10.2174/157340208786241336
|View full text |Cite
|
Sign up to set email alerts
|

Role of Reactive Oxygen Species in Tumor Necrosis Factor-alpha Induced Endothelial Dysfunction

Abstract: Endothelial cell injury and dysfunction are the major triggers of pathophysiological processes leading to cardiovascular disease. Endothelial dysfunction (ED) has been implicated in atherosclerosis, hypertension, coronary artery disease, vascular complications of diabetes, chronic renal failure, insulin resistance and hypercholesterolemia. Although now recognized as a class of physiological second messengers, reactive oxygen species (ROS) are important mediators in cellular injury, specifically, as a factor in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(101 citation statements)
references
References 129 publications
8
89
0
4
Order By: Relevance
“…Thus the animals showed decreased responses to adrenergic nerve stimulation and increased NANC-and endothelium-dependent relaxation that were associated with increased corporal eNOS and nNOS protein levels (Carneiro et al, 2009). TNF-␣ impaired endothelium-dependent and NOmediated vasodilation in various vascular beds (Chen et al, 2008;Zhang et al, 2009a), and a key role for TNF-␣ in mediating endothelial dysfunction in ED has been suggested (Carneiro et al, 2009). Blockade of TNF-␣ actions (which is clinically possible) may theoretically represent an alternative therapeutic approach for erectile dysfunction, especially in pathological conditions associated with increased levels of this cytokine.…”
Section: Adrenomedullin Calcitonin Gene-related Peptidementioning
confidence: 98%
See 1 more Smart Citation
“…Thus the animals showed decreased responses to adrenergic nerve stimulation and increased NANC-and endothelium-dependent relaxation that were associated with increased corporal eNOS and nNOS protein levels (Carneiro et al, 2009). TNF-␣ impaired endothelium-dependent and NOmediated vasodilation in various vascular beds (Chen et al, 2008;Zhang et al, 2009a), and a key role for TNF-␣ in mediating endothelial dysfunction in ED has been suggested (Carneiro et al, 2009). Blockade of TNF-␣ actions (which is clinically possible) may theoretically represent an alternative therapeutic approach for erectile dysfunction, especially in pathological conditions associated with increased levels of this cytokine.…”
Section: Adrenomedullin Calcitonin Gene-related Peptidementioning
confidence: 98%
“…A candidate factor in causing ROS production in endothelial cells is tumor necrosis factor ␣ (TNF-␣). TNF-␣ has been shown to play an important role in CV disease, mainly because of its direct effects on the vasculature (Chen et al, 2008;Zhang et al, 2009a), and may also be involved in ED, because high levels of TNF-␣ were demonstrated in patients with ED (Carneiro et al, 2010). TNF-␣ KO mice were found to exhibit changes in cavernosal reactivity that would facilitate erectile responses.…”
Section: Adrenomedullin Calcitonin Gene-related Peptidementioning
confidence: 99%
“…The excessive production of TNF [30] has a deleterious downstream effect by augmentation of ROS production [31] and limiting NO bioavailability in endothelial cells, which results in reducing NO-dependent vasodilation in vascular smooth muscle cells. Our laboratory is focusing on anti-inflammatory and antioxidative stress therapeutic effects, and the roles of sodium salicylate [22] , exercise and resveratrol [24,25] in type 2 diabetes [18,19,[21][22][23]27] , I/ R injury [13][14][15][16] , obesity [17] and atherosclerosis [28,32] .…”
Section: Resultsmentioning
confidence: 99%
“…Within the peripheral blood, DNA single-and double-stranded breaks accompanied by oxidative base damage were most evident in CD4 + and CD8 + T cells after 1-h TNF-α treatment and to a lesser extent CD19 + B cells versus CD11b + cells or the eluate, indicating differing susceptibility to DNA damage. DNA single-and double-stranded breaks measured by the alkaline comet assay and immunostaining for γH2AX foci were significantly higher in T cells; however, only DNA double strand breaks were significantly higher in CD19 + B cells T-cell lymphomas, due to persistent systemic genotoxicity to T cells and peripheral lymphoid organs, which manifested significant amounts of DNA damage [46]. Research has shown that elevated levels of circulating cytokines characteristic to intestinal inflammation such as TNF-α and their downstream mediators are partially responsible for inducing DNA damage [47].…”
Section: Immune Complex Mediates Molecular Interactionsmentioning
confidence: 90%